Eksplorasi Sumber Imajinasi Mahasiswa tentang Profesi Dokter - Yoga Pamungkas Susani; Gandes Retno Rahayu; Rossi Sanusi; Yayi Suryo Prabandari; Harsono Harsono (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2015)
Background: In the process of becoming a doctor, a medical student experiencing the development of professional identity. In this process, students need a broad picture of  medical profession. They need to orient themselves in the medical profession to determine the future professional identity as a doctor. Source of the picture of medical profession needs to be explored further. This study aims to explore the ways students get picture of the medical profession.Method: Qualitative research by conducting in-depth interviews to 17 preclinical and clinical medical students. Determinants and emergent coding performed to analyze the results of the interview.Results: Source of imagination can be derived from the curriculum and outside the curriculum. Students get two important things, first was overview of the work environment and how the physician work and second was physician professional values. Characters of role models identified primarily from student interaction with faculties. The characters include faculty’s role as teacher, as doctor, their personal atributes and how they interact with students.Conclusion: Formal curriculum plays important roles in providing and facilitating students to get overview about the work environment and how the doctors work in the health service. Although the transfer of professional value to students is determined by the hidden curriculum, but the formal curriculum can facilitate by providing activities that allows the interaction between generations or conduct review on fiction and non-fiction medical stories and histories that is obtained from media.